2015
DOI: 10.1590/1982-7849rac20151410
|View full text |Cite
|
Sign up to set email alerts
|

Valor da tecnologia da informação na firma: estudo com empresas brasileiras

Abstract: Estudos realizados no início de 2000, a partir de dados objetivos de desempenho, confirmaram o valor da Tecnologia da Informação (TI) diretamente no nível da firma (A. S. Bharadwaj, 2000; Santhanam & Hartono, 2003). Contudo, a literatura recente tem sinalizado para resultados distintos, tendo em vista a padronização na oferta de produtos e serviços de TI. Na perspectiva da Teoria Baseada em Recursos, o artigo testa se o valor da TI continua a ser captado pelas medidas de desempenho da firma, conforme estud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
2
0
3
Order By: Relevance
“…E. Chan & Huff, 1992) e, ao alinhar, integrar, suportar e executar a estratégia, e estudo recentes (Marabelli & Galliers, 2017;Peppard, Galliers, & Thorogood, 2014;Whittington, 2014) destacam contribuição em habilitar a estratégia-como-prática nas organizações. A contribuição do SIS gera diversos benefícios para organização (Albertin & Albertin, 2012;Coltman, Tallon, Sharma, & Queiroz, 2015), proporcionando produtividade, vantagem competitiva, crescimento e desempenho organizacional (Oliveira, Maçada, & Oliveira, 2014;Y. Chen et al, 2014;Yoshikuni & Albertin, 2017) para enfrentar os desafios dos ambientes complexos e dinâmicos (Merali et al, 2012;Mikalef & Pateli, 2017).…”
Section: Strategic Information Systemsunclassified
“…E. Chan & Huff, 1992) e, ao alinhar, integrar, suportar e executar a estratégia, e estudo recentes (Marabelli & Galliers, 2017;Peppard, Galliers, & Thorogood, 2014;Whittington, 2014) destacam contribuição em habilitar a estratégia-como-prática nas organizações. A contribuição do SIS gera diversos benefícios para organização (Albertin & Albertin, 2012;Coltman, Tallon, Sharma, & Queiroz, 2015), proporcionando produtividade, vantagem competitiva, crescimento e desempenho organizacional (Oliveira, Maçada, & Oliveira, 2014;Y. Chen et al, 2014;Yoshikuni & Albertin, 2017) para enfrentar os desafios dos ambientes complexos e dinâmicos (Merali et al, 2012;Mikalef & Pateli, 2017).…”
Section: Strategic Information Systemsunclassified
“…Regarding the motivational theme, specifically the central concepts, diverse materials related to these perspectives can be found about work places, aside from psychological applications in different scenarios (Bergamini, 1990; Franco, 2008; Maruping & Magni, 2015; Maslow, 2003; Spector, 2006). There is a large amount of material on technology use; most studies focus on managerial use in organizations (Albertin & Albertin, 2012; Domingues, Palmisano, Rosini, & Silva, 2015; Lunardi, Dolci, & Maçada, 2010; Oliveira, Maçada, & Oliveira, 2015), but none of them analyzes the consumer or his/her behavior when making use of collaborative technology.…”
Section: Introductionmentioning
confidence: 99%
“…With this term, they indicated that it was not only an intensity in the use of "computers" that increased wealth generation, but pointed to the importance of a new way of organizing work, and as such, opened a wide field of research. Oliveira et al (2015) investigated the benefits of IT investment from a sample of one hundred and forty-nine Brazilian companies. In their analysis, based on Resource-Based Theory (Barney, 1991), they were unable to establish a difference between the performance of companies with higher IT installed capacity, and those with lower capacity.…”
Section: Introductionmentioning
confidence: 99%